Prospective Study of Muscle Injuries in Three Consecutive Seasons of the Brazilian Football Championship - Gabriel Furlan Margato; Edilson Ferreira Andrade Júnior; Paulo Henrique Schmidt Lara; Jorge Roberto Pagura; Moisés Cohen; Gustavo Gonçalves Arliani (Revista Brasileira de Ortopedia, 2021)
Abstract Objective To perform a prospective evaluation of muscle injuries that occurred during the matches of series A and B of the Brazilian Men's Football Championship from 2016 to 2018. Prospective A prospective-cohort study with data collection regarding muscle injuries that occurred during the official matches of the first and second divisions of the Brazilian Men's Soccer Championship in the 2016, 2017 and 2018 seasons. Results The total number of muscle injuries was of 577 throughout the 3 seasons, with a gradual and annual reduction in the incidence of injuries (219 injuries in 2016, 195 in 2017, and 163 in 2018), with a statistically significant difference between the 2016 and 2018 seasons. Muscle injuries represented approximately 35% of the total lesions. The incidence of muscle injuries was of 7.66 per 1,000 hours of play. During the 3 seasons (2016 to 2018), the most common injury was of the hamstring muscle (41.1%, 40.5%, and 33.7% respectively). Wingers were the most affected players, and the most common injury severity scale was moderate (8 to 28 days). The moment of the match with the highest incidence of injuries was in the period between 61 and 75 minutes, with an index of 19.9%, with no statistical difference in relation to the other periods of the match. Conclusion There was an incidence of muscle injuries of 7.7 /1,000 h, and they occurred predominantly in home games, in defenders (wingers and centre-backs), with an average age of 28 years, mainly involving the hamstring muscles, with a moderate mean time of absence (8 to 28 days).